Factors influencing young adults’ debt in Malaysia - Abdul Adzis, Azira; Abu Bakar, Juhaida; Kadir @ Shahar, Hanita (Academy of Business and Retail Management Research, 2017)
This study explores factors affecting debt level among young adults in Malaysia.Previous studies have linked material values, money management skills, and economic factors to credit card debt and student debt, but this study extends the previous research by investigating various forms of consumers’ debt in an emerging market where vulnerable youths are frequently bombarded with materialistic media messages that trigger their spending behaviour.In particular, variables such as pursuits of materialistic attitudes, money management attributes, and income level are examined in this study to see whether they are predictors of youth debt in Malaysia.A self-administered survey on 629 respondents centered around northern part of Malaysia was conducted based on convenience and judgmental sampling techniques.The findings suggest that money management skills and income level significantly influence the debt level of Malaysian young adults. Interestingly, materialism variable is insignificant, implying that young Malaysians represented in this sample do not possess materialistic attitude that lead to indebtness. The findings provide insights to the policy maker and the government to inculcate awareness of basic money management skills to ensure that the younger generation does not fall into the state of excessive debt which could lead to financial insolvency.